2014
DOI: 10.1111/cbdd.12260
|View full text |Cite
|
Sign up to set email alerts
|

Two‐ and Three‐dimensional Rings in Drugs

Abstract: Using small, flat aromatic rings as components of fragments or molecules is a common practice in fragment-based drug discovery and lead optimization. With an increasing focus on the exploration of novel biological and chemical space, and their improved synthetic accessibility, 3D fragments are attracting increasing interest. This study presents a detailed analysis of 3D and 2D ring fragments in marketed drugs. Several measures of properties were used, such as the type of ring assemblies and molecular shapes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
186
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 277 publications
(201 citation statements)
references
References 21 publications
0
186
0
2
Order By: Relevance
“…4752 On one hand, 3D-shaped fragments have been suggested to be capable of sampling a larger chemical space 50 and of exploring the pocket space of targets more extensively than 2D-shaped fragments, 48 being more likely to deliver biologically active and clinically relevant molecules. 51,52 On the other hand, 3D-shaped fragments have raised questions about the implications that their implicit higher molecular complexity can have for hit rates 53 and for ease of synthesis and derivatization. 54 It has also been shown that three-dimensionality can be introduced, to different degrees depending on the connectivity of the fragment scaffold, during fragment elaboration.…”
Section: Resultsmentioning
confidence: 99%
“…4752 On one hand, 3D-shaped fragments have been suggested to be capable of sampling a larger chemical space 50 and of exploring the pocket space of targets more extensively than 2D-shaped fragments, 48 being more likely to deliver biologically active and clinically relevant molecules. 51,52 On the other hand, 3D-shaped fragments have raised questions about the implications that their implicit higher molecular complexity can have for hit rates 53 and for ease of synthesis and derivatization. 54 It has also been shown that three-dimensionality can be introduced, to different degrees depending on the connectivity of the fragment scaffold, during fragment elaboration.…”
Section: Resultsmentioning
confidence: 99%
“…[18] As a flexible structure, the saturated ring system has the ability to adopt multiple conformations and to project substituents into optimal orientations within the binding pocket. Therefore, optimization of the core began by replacement of the A- and/or Bring of the biphenyl core with a saturated ring system.…”
Section: Resultsmentioning
confidence: 99%
“…[38,39] 2.1. [44] The alignment of drug-like properties and selectivity remains am ajor challenge. [40] It is known that the chemical structure of ad rug correlates with its physicochemical properties, i.e.,i ts drug metabolism pharmacokinetics /a bsorption, distribution, metabolism, and excretion-toxicity (DMPK/ADMET) profile, pertaining to Lipinski's rules [41] and ultimately its pharmacological activity.…”
Section: Psychoactive Drugs (Psychotropics)mentioning
confidence: 99%